E-Katalog Sebagai Sistem Informasi Pemasaran Kopi Sapit Berbasis Web - Dina Yulistina; Baiq Desi Dwi Arianti (Universitas Hamzanwadi, 2019)
This studyaims to develop e-catalog as a web-based marketing information system for Sapit coffee and to determine the feasibility of e-catalog marketing of sapit coffee. This type of research uses the method of RD (Research and Development). The feasibility trial of the learning media was carried out by 2 media experts and 2 material experts, as well as 20 visitors to the web-based sapit coffee marketing e-catalog. Obtained the percentage of eligibility from media experts by 71% by looking at 3 aspects, namely the appearance of the media, functionality, and visual communication so that it is declared